Impact Investing in Südafrika: In Ermächtigung investieren und Investoren ermächtigen - (:unkn) unknown (My University, 2020)
This paper examines how Impact Investment (II) becomes part and transforms structured accumulation regimes and circuits, with a particular emphasis on South Africa's agricultural sector. Through the joint implementation of a macro study of the South African II circuits, and a micro study of a particular II fund’s practices and impacts, the paper develops an in-depth political economy assessment of II circuits in order to historicize these circuits, to map the South African II community, and to characterize the power balances presently structuring it. Rather than highlighting ruptures, it draws the attention to the historical continuities and path-dependencies as II related tools are rooted into older financial practices, shaping today's II development and practice - hence questioning II as a tool for empowerment.
Keywords: African Research